A Synthetic, Species‐Specific Activator of Secondary Metabolism and Sporulation in Streptomyces coelicolor. Issue 1 (13th December 2012) - Ahmed, Salman; Craney, Arryn; Pimentel‐Elardo, Sheila M.; Nodwell, Justin R.
Abstract The secondary metabolites produced by bacterial species serve many clinically useful purposes, and Streptomyces have been an abundant source of such compounds. However, a poor understanding of their regulatory cascades leads to an inability to isolate all of the secondary metabolites this genus is capable of producing. This study focuses on comparing synthetic small molecules that were found to alter the production of secondary metabolites in Streptomyces coelicolor. A survey of these molecules suggests that each has a distinct mechanism of action, and hence, could be used as a unique probe of secondary metabolism. A comparative analysis of two of these molecules, ARC2 and ARC6, confirmed that they modulate secondary metabolites in different ways. In a separate study, ARC2 was shown to give rise to a different phenotype through the inhibition of a target in fatty acid biosynthesis. The results of this study suggest that ARC6 does not have the same target, although it might target the same metabolic system. Furthermore, the results demonstrate that ARC2 and ARC6 act through distinct mechanisms and further suggest that chemical probes can be important tools in enhancing our understanding of secondary metabolism and the streptomycete life cycle.